Doing well by doing good? Community development venture capital - Anna Kovner; Josh Lerner (Federal Reserve Bank of New York, 2012)
This paper examines the investments and performance of community development venture capital (CDVC). We find substantial differences between CDVC and traditional venture capital (VC) investments: CDVC investments are far more likely to be in nonmetropolitan regions and in regions with little prior venture capital activity. Moreover, CDVC is likely to be in earlier-stage investments and in industries outside the venture capital mainstream that have lower probabilities of successful exit. Even after we control for this unattractive transaction mix, the probability of a CDVC investment being successfully exited is lower. One benefit of CDVCs may be their effect in bringing traditional VC investment to underserved regions: When we control for the presence of traditional VC investments, each additional CDVC investment results in an additional 0.06 new traditional VC fi rm in a region.
Keywords: G20; G24; G28; 330; community development; venture capital